Increasing burden of necrotizing otitis externa: our experience of 38 cases - Lambor, Dheeraj; Naik, Kanhai R.; DeSa, Carnegie; Lambor, Swati; Samuel, Ruby (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Necrotizing otitis externa is an infection affecting immune-compromised and elderly diabetic patients resulting in complications with significant morbidity and mortality. We present our experience with this disease, along with the investigative tools and treatment modalities that benefitted most. The objective being to analyze the course of the disease and the benefit of having an institutional protocol for its management. Methods: This is a retrospective observational study on patients diagnosed with necrotizing otitis externa between 2013-2019. Results: Out of 38 patients 36 were diabetics, the commonest clinical presentation included otalgia in 37 patients, granulations in 35, facial nerve palsy in 14 and Pseudomonas aeruginosa was isolated in 19 patients. They were managed with multidrug combination antibiotic therapy, topical dressing and drops with 27 showing improvement. Conclusions: We recommend a diagnostic triad for NOE comprising of otalgia in an elderly diabetic patient with granulations in the external auditory canal. It is best managed by controlling diabetes, appropriate antibiotic combination, topical dressing, and sometimes surgical debridement.